Mechanism to identify, define and prioritize interdisciplinary forest research themes at national, regional and global levels - Glück, P.; Byron, R.N. (Federal Ministry of Agriculture and Forestry, 1998)
This paper describes how to sets of factors-the economic characteristics of the benefits of research, and the policy network of diverse actors and their interests-determine not only the priorities for (interdisciplinary) forest research themes but also the choice of mechanisms for the decision-making process itself. The paper extends the literature in organisation theory and political science, to propose a theoretical framework to guide the identification, definition, and prioritisation of interdisciplinary forest research themes at the global level. Such a framework seems necessary if proposals before the Intergovernmental Forum on Forests for supporting and coordinating international forestry research, are to succeed. The paper leads to the conclusion that international deliberations on forests would benefit substantially from a new kind of formal arrangement for providing scientific input. For example, a scientific advisory body could help to bridge the gap between the information needs of negotiators and policy makers and the scientific and research community